Safety Assessment of Water-Extract Sericin from Silkworm (Bombyx mori) Cocoons Using Different Model Approaches. (6th November 2020) - Qin, Huiyan; Zhang, Jiehong; Yang, Hui; Yao, Siyu; He, Li; Liang, Huili; Wang, Yanwu; Chen, Huafeng; Zhao, Peng; Qin, Guangqiu
Abstract : Sericin is a natural protein component of silks of silkworm and has potential utility in multiple areas such as pharmacological, cosmetics, and biotechnological industries. However, the understanding of its toxicological safety is still limited. This study evaluated the safety of water-extract sericin from silkworm ( Bombyx mori ) cocoons using different model approaches, including three genotoxicity studies (the bacterial reverse mutation test, the mammalian erythrocyte micronucleus test, and the mouse spermatogonia chromosomal aberration test) and a 90-day subchronic toxicity study in Sprague-Dawley (SD) rats. The results of this study showed that water-extract sericin was nonmutagenic and nongenotoxic both in vitro and in vivo . Sericin did not induce significant changes in the body and organ weight, food intake, blood hematology and serum biochemistry, urine index, and histopathology in rats. The NOAEL of sericin was determined to be 1 g/kg/day for male and female rats. These results indicated that water-extract sericin was of low toxicity in the experimental conditions of the current study and had the potential for application in food-related products.